2020
DOI: 10.29328/journal.cjog.1001055
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic shock due to irreducible uterine torsion in a third trimester twin pregnancy: A case report

Abstract: Uterine torsion is a rare life-threatening event that happens at any age or any gestational age. By defi nition, it consists of a rotation of more than 45 degrees around the long axis of the uterus. The reported cases have variable presentations. The uterine torsion can happen without any sequelae either for the fetus or the mother. However, fetal and maternal mortalities were also reported in such a case We hereby, report the case of a 29-year-old female patient, with previous four Normal Vaginal Deliveries, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In our literature review, one maternal death was reported since 2006. 6 UT could reduce the uterine blood flow leading to a decrease of placental perfusion 22 and contributing to the process of IUGR and Doppler-velocimetry alterations of the reported case report. To our knowledge, this is the second case in literature suggesting this correlation.…”
Section: Discussionmentioning
confidence: 72%
“…In our literature review, one maternal death was reported since 2006. 6 UT could reduce the uterine blood flow leading to a decrease of placental perfusion 22 and contributing to the process of IUGR and Doppler-velocimetry alterations of the reported case report. To our knowledge, this is the second case in literature suggesting this correlation.…”
Section: Discussionmentioning
confidence: 72%